LEGAL RECONSTRUCTION OF VILLAGE FUND SUPERVISION MODEL IN VILLAGE GOVERNMENT BASED ON THE PRINCIPLE OF TRANSPARENCY - Rizky Darmawansyah Sihombing (NOMOI Law Review, 2023)
The state revenue and expenditure budget (APBD) is part of village income sources that are included in village finances. The state revenue and expenditure budget (APBD) that is given is usually called village funds. Village funds are funds originating from the State Revenue and Expenditure Budget earmarked for Villages which are transferred through the district/city Regional Revenue and Expenditure Budget and are used to finance government administration, development implementation, community development, and community empowerment. The large amount of the budget given to each village certainly needs to be monitored to avoid abuse of power. In addition to the need for supervision, the village government also needs to always be principled and adhere to the principle of openness so that the community knows and is involved in controlling the implementation of village governance. So that the high level of corruption that occurs in the village government environment requires us to evaluate and reconstruct the monitoring system that must be carried out.